2011
DOI: 10.1063/1.3653974
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio properties of Li-group-II molecules for ultracold matter studies

Abstract: We perform a systematic investigation of the electronic properties of the 2 Σ + ground state of Lialkaline-earth dimers. These molecules are proposed as possible candidates for quantum simulation of lattice-spin models. We apply powerful quantum chemistry coupled-cluster method and large basis sets to calculate potential energies and permanent dipole moments for the LiBe, LiMg, LiCa, LiSr, and LiYb molecules. Agreement of calculated molecular constants with existing experimental data is better than or equal to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 50 publications
6
50
1
Order By: Relevance
“…[20] showed that the ground-state contribution dominates for a heavy v = 0, j = 0 RbCs molecule and is small but nonnegligible for the lighter KRb. The LiYb molecule has a very small permanent dipole moment of 0.011ea 0 [45] at equilibrium separation R e = 6.71a 0 and transitions to the electronically excited states dominate. Here, e is the charge of the electron.…”
Section: Atom-dimer Dispersion Potentialsmentioning
confidence: 99%
See 2 more Smart Citations
“…[20] showed that the ground-state contribution dominates for a heavy v = 0, j = 0 RbCs molecule and is small but nonnegligible for the lighter KRb. The LiYb molecule has a very small permanent dipole moment of 0.011ea 0 [45] at equilibrium separation R e = 6.71a 0 and transitions to the electronically excited states dominate. Here, e is the charge of the electron.…”
Section: Atom-dimer Dispersion Potentialsmentioning
confidence: 99%
“…In this paper we use the spectroscopicallyaccurate X 1 Σ + g potential for Li 2 [44] and our previously determined ab initio X 2 Σ + potential for LiYb [45]. Both pair-wise potentials were expanded to large internuclear separation using the best-known van der Waals coefficients [50,51].…”
Section: Trimer Potential Energy Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…The ground Yb( 1 S 0 )+Li( 2 S 1/2 ) state potential was calculated in one of our earlier papers [26] using a nonrelativistic coupled cluster method. We presented its long-range van der Waals coefficient separately in [13].…”
Section: A Ab-initio Calculation Of Molecular Potentialsmentioning
confidence: 99%
“…1 (b). In the following we illustrate a basic encoding scheme for the case of a molecule with a 2 Σ ground state [54], where states |g and |e are represented in two Zeeman sublevels of two excited rotational states. However, we point out that recently several other schemes for tunable dipoledipole interactions for spin and/or rotational degrees of freedom [37,42,43] have been suggested which could also be adapted for the present purpose.…”
Section: Molecular Spin Qubitsmentioning
confidence: 99%